THE RELATIONSHIP OF NETWORK QUALITY AND CUSTOMER SUPPORT TOWARDS CUSTOMER SATISFACTION FOR MOBILE TELECOMMUNICATION INDUSTRY IN INDONESIA - Mulyadi, Dedi; Dimala, Cempaka Putrie; Sinaga, Obsatar; Mohamad Yazid, Mohd Faizun (International Journal of Psychosocial Rehabilitation, 2020)
The purpose of this study is to measure the relationship between the network quality and customer support towards customer satisfaction. The penetration rate for telecommunication have reached almost to the maximum and there are more options to customer in selecting their preferred service provider. At the point of stiff competition, service provider need to carefully assess their service quality especially related to network and customer support. This study was conducted using Seven-Likert scale questionnaires with a total of 300 respondents from various demographic. The results were analyzed using Cronbach’s α, Pearson’s correlation and regression analysis techniques. The results of the research showed that network quality and customer support affects the customer satisfaction. The research presents a comprehensive framework enabling mobile service providers to understand the factors affecting consumer satisfaction. In terms of practical implication, manager of customer services or customer experiences may look at the result for their strategic marketing activities.